Influence of an extended education program on the knowledge of cardiovascular risk factors among subjects undergoing rehabilitation following acute coronary syndrome - Kapko, Wojciech S.; Krzych, Łukasz (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2016)
Introduction : Health education is a component of complex cardiac rehabilitation (CCR). Aim : To evaluate the influence of an authorial extended educational program on the knowledge of cardiovascular risk factors among subjects undergoing early in-hospital rehabilitation following acute coronary syndrome treated with percutaneous intervention. Material and methods: This prospective study covered 205 consecutive subjects (153 men and 52 women, aged 62 ±9 years) undergoing CCR. They were randomly allocated to the control group (105 patients receiving standard education during CCR) or the study group (100 patients participating in the extended education program). The extended education program was conducted in the 2nd and 3rd week of CCR and included a package of educational materials and additional lectures. Results : Knowledge of basic rules for secondary cardiac prevention was better in the study group, both on admission and after CCR. Notwithstanding, a positive influence of the extended educational program was found with regard to awareness of recommended blood pressure levels and blood lipid profile (improvement of 15–20% in the study group). At baseline, the knowledge of risk factors was comparable between the groups (the percentage of correct questionnaire answers was 50 ±17% among the controls vs. 49 ±16% in the study group; p = 0.77), but improved significantly after education (52 ±17% among controls vs. 58 ±19% in the study group; p = 0.009) and remained better in the study group after a 3-month follow-up (56 ±19% among controls vs. 64 ±19% in the study group). Conclusions: Extended education during CCR significantly improves the knowledge of cardiovascular risk factors in patients after acute coronary syndrome.